University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.2 - The Derivative as a Function - Exercises - Page 125: 23


$f'(x) = \frac{-1}{(x+2)^{2}}$

Work Step by Step

$f(x) = \frac{1}{x+2}$ $f'(x) = \lim\limits_{z \to x}\frac{\frac{1}{z+2} - \frac{1}{x+2}}{z-x}$ $f'(x) =\lim\limits_{z \to x}\frac{1}{z-x}\frac{x-z}{(z+2)(x+2)}$ $f'(x) =\lim\limits_{z \to x}\frac{-1}{(z+2)(x+2)}$ $f'(x) = \frac{-1}{(x+2)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.